Aktivasi Green Coke Menjadi Karbon Aktif Menggunakan KOH Sebagai Aktivating Reagent - Rahmawati Rahmawati; Irdoni HS; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The activated carbon is one of adsorbent which often used in absorption process. This is because the activated carbon has better absorptive capacity of adsorption and surface areathan other adsorbent. One of the potentially material that can be used as a raw material to be activated carbon is green coke because it has 87- 97% carbon content and 250-3000 m2/grsurface area. This research aims to determine the effect of mass comparison of KOH to green coke, and activation time to the characterization of activated carbon. The manufacture ofactivated carbon was carried out with chemical activation method which used KOH as activating reagents. The process was done by mixing the green coke and KOH with a mass ratio variation (1/1; 2/1; 3/1 b/b) and activation time (18, 20, 22 hours). The activatedcarbon was analyzed with proximate analysis (moisture, ash, volatile), activated carbon absorption of the methylene blue, the surface area of BET (Brunauer Emmett Teller) and analysis by using Design Expert v10.0.1. The mass comparison of KOH to green coke and activation time indicated a significant effect to all of responses. On the best condition process (KOH mass comparison to green coke is 3.414:1 and activation time 20 hours) was obtained the best response value for mass yield 85.9%,; water content 7.37%; ash content 3.22%; volatile substance content 6.8%; the absorption of activated carbon to the methylene blue is 137.15 mg/g and surface area is 25,33 m2/gr. The analysis result of surface area determine that KOH mass comparison to green coke and activation time has significant effect to the surface area, it is indicated by the pores which increasingly open and the enhancement of surface area before activationKeyword : activated carbon, chemical treatment, green coke